2019
DOI: 10.1002/er.4379
|View full text |Cite
|
Sign up to set email alerts
|

A review on thermal energy storage systems in solar air heaters

Abstract: Summary The drying needs of agricultural, industrial process heat requirements and for space heating, solar energy is one of the prime sources which is renewable and pollution free. As the solar energy is inconsistent and nature dependent, more often there is a mismatch between the solar thermal energy availability and requirement. This drawback could be addressed to an extent with the help of thermal energy storage systems combined with solar air heaters. This review article focuses on solar air heaters with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 81 publications
0
25
0
2
Order By: Relevance
“…Moreover, outdoor temperature changes and daily solar energy can be retrieved using passive solar grids including thermal energy storage (TES) setups . In this regard, compared with sensible heat‐based systems, the popularity of latent heat‐based TES frameworks working by phase change materials (PCMs) is increased day by day because they allow higher heat storage per volume and also provide better management to the released heat …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, outdoor temperature changes and daily solar energy can be retrieved using passive solar grids including thermal energy storage (TES) setups . In this regard, compared with sensible heat‐based systems, the popularity of latent heat‐based TES frameworks working by phase change materials (PCMs) is increased day by day because they allow higher heat storage per volume and also provide better management to the released heat …”
Section: Introductionmentioning
confidence: 99%
“…Recovering and reusing waste energy is one of the most effective methods for energy conservation and thermal pollution reduction. The purpose of thermal energy storage (TES) is to store heat under specific conditions and release it at a later stage when required . Sensible energy storage, latent energy storage, and chemical energy storage are all included in TES.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of thermal energy storage (TES) is to store heat under specific conditions and release it at a later stage when required. 1,2 Sensible energy storage, 3 latent energy storage, 4 and chemical energy storage 5 are all included in TES. The use of phase change materials (PCMs) is an effective latent energy storage technique because of the large storage capability, high thermal conductivity, and isothermal phase transition temperature PCMs have.…”
Section: Introductionmentioning
confidence: 99%
“…7 Research and development of integration of solar air heater with thermal energy storage material have become the main focus in the field of solar engineering technology. 10,11 A review study of thermal energy storage integration with solar heaters has been conducted by Haldorai et al 12 From the study, it is concluded that solar heaters with latent heat energy storage material as a thermal energy storage component provide a better thermal efficiency when compared with solar heaters employing other types of thermal energy storage materials. The method of latent heat with the application of phase change material (PCM) has received a special attention because of its higher energy storage density compared with sensible heat energy storage material.…”
Section: Introductionmentioning
confidence: 99%
“…Methods of storing thermal energy including sensible heat and latent heat have been employed. Many solar air heater applications using latent heat energy storage materials such as hydrated salt, 13 palmitic and lauric acid, 14,15 and technical grade paraffin wax 11,12 have been studied. 8,9 It works on the principle where the material itself will store and release an amount of heat when the phase changes during the operation.…”
Section: Introductionmentioning
confidence: 99%